Penguatan Pemahaman Publikasi Ilmiah bagi Mahasiswa - M. Iqbal Liayong Pratama; Daud Yusuf; Sri Maryati; Ramla Hartini Melo; Nurfaika Nurfaika; Syarifah Fatimah Setiasih Niode; Djamal Adi Nugroho Uno (Universitas Negeri Gorontalo, 2026)
Scientific publication is an essential research output that serves as a medium for disseminating research findings while strengthening academic culture in higher education. However, many students still have limited understanding of the publication process, particularly in preparing journal articles, selecting appropriate journals, understanding publication ethics, and submitting manuscripts through the Open Journal System (OJS). This community engagement program aimed to strengthen the understanding of scientific publication among students of the Geography Study Program, Universitas Negeri Gorontalo, as the final output of their research. The program was conducted through lectures, interactive discussions, question-and-answer sessions, and the sharing of publication experiences. Evaluation was carried out through observation of participants' engagement during the activity and feedback collected at the end of the session. The results showed that participants developed a better understanding of scientific article structure, publication ethics, journal selection strategies, reference management applications, and manuscript submission through OJS. This activity is expected to improve students' readiness to publish their research findings and foster a stronger culture of scientific publication within the university.